Dielectric response of Al-substituted multiferroic TbMnO3 at high temperatures. Issue 1 (January 2015) - Izquierdo, J.L.; Astudillo, A.; Bolaños, G.; Zapata, V.H.; Morán, O.
Abstract: Multiferroic Tb1− x Al x MnO3 ( x =0, 0.1, 0.2) was prepared using the standard solid-state reaction. The dielectric properties of these samples were investigated over wide ranges of frequencies and temperatures ( T ≥300 K) by means of complex impedance spectroscopy. The isovalent substitution of Al 3+ for Tb 3+ distinctly influences the structural and dielectric properties of the parent TbMnO3 . The conductivity data of the undoped and Al-doped samples fit well to Jonscher׳s law σac ( ω )= σ dc + Aω n . The resulting fitting parameters indicated that the hopping process occured between neighboring sites. The conductivity in the dc regime followed an Arrhenius relation with activation energies of 0.26 and 0.12 eV for undoped and Al-doped ( x =0.1) samples, respectively. In turn, the ac conductivity was well described by the small polaron hopping model, with energies of 0.2 and 0.14 eV for undoped and Al-doped ( x =0.1) samples, respectively. The real part of the dielectric permittivity ( ε ′) increased with increasing temperature and lowering frequency. The value of ε ′ also increased with the Al doping. The occurrence of a non-Debye-type relaxation was verified for the studied samples. The relaxation dynamics of charge carriers in the samples was examined within the electric modulus formalism, which allowed determining the most probable relaxation time and the respective activation energy for the dielectric relaxation. In the temperature range 300–425 K, the activation energy for the dielectric relaxation was calculated as 0.25 eV and 0.16 eV for undoped and Al-doped ( x =0.1) samples, respectively. The imperfect overlapping of the reduced plots of the modulus curves on a single master curve, particularly at higher frequencies, for all the temperatures and Al concentrations considered, suggests that the behavior of the dynamic processes is slightly temperature- and Al-content-dependent. Finally, the impedance spectra, characterized by the appearance of semicircle arcs, were well modeled in terms of equivalent electrical circuits.